2015
DOI: 10.22146/ijc.21211
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Cadmium Toxicity to Marine Phytoplankton, <i>Chaetoceros gracilis</i> and <i>Isochrysis</i> sp.

Abstract: In Copper (Cu) based antifouling (AF) paints Cu was largely used as booster biocide after organotin was banned. Cu is micronutrient which is important in photosynthesis process

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Neither limiting nor toxic effects of Cu on phytoplankton and zooplankton growth are included in the present model configurations. Laboratory assessments of Lowest Observed Effect Concentration and No Observed Effect Concentration, which are necessary to assess toxic Cu concentrations, are rare (see, e.g., Suratno et al, ). Representing both the limitation and toxicity effects of Cu on plankton growth in PISCES relies on deeper knowledge on physiological effects of Cu and on estimations of concentration thresholds for limiting and toxic effects (Prosnier et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Neither limiting nor toxic effects of Cu on phytoplankton and zooplankton growth are included in the present model configurations. Laboratory assessments of Lowest Observed Effect Concentration and No Observed Effect Concentration, which are necessary to assess toxic Cu concentrations, are rare (see, e.g., Suratno et al, ). Representing both the limitation and toxicity effects of Cu on plankton growth in PISCES relies on deeper knowledge on physiological effects of Cu and on estimations of concentration thresholds for limiting and toxic effects (Prosnier et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In an experiment on Chaetoceros gracilis and Isochrysis sp. marine microalga, the reciprocal toxicity of Cd and Cu was determined [55]. Using the IC50 test for 96 h to estimate growth inhibition, it was reported that Cd (IC50 = 2.370 mg L −1 ) was more toxic to C. gracilis than to the growth of Isochrysis sp.…”
Section: Previous Investigations Performed To Determine Reciprocal To...mentioning
confidence: 99%
“…Di Indonesia, jenis fitoplankton yang telah banyak digunakan adalah jenis yang hidup di kolom air seperti C. gracilis (Puspitasari & Hindarti, 2009, Puspitasari, 2011, Puspitasari & Lestari, 2014, Isochrysis sp (Puspitasari & Purbonegoro. 2011;Suratno et al, 2015) Salah satu fitoplankton bentik yang sudah dipelihara di Pusat Penelitian Oseanografi adalah jenis diatom bentik, Nitszschia sp. Diatom bentik adalah organisme microphytobenthos dan berperan sebagai sumber utama makanan bagi meiofauna.…”
Section: ) Kelompok Penelitian Pencemaran Dan Bioremediasi Pusat Peunclassified